Application of Actor-Network Theory to Network Neutrality in Korea - Dong-Hee Shin; Hyup (Henry) Kim; Nam Cheol Kim; So Jeong Kim; Sungho Kim; Guri Kim (International Telecommunications Society (ITS), 2015)
This research analyzes the debate surrounding the network neutrality in Korea through the lens of Actor-Network Theory (ANT), trying to map the socio-technical network formed around the network neutrality controversy. We intend to reassemble the heterogeneous elements involved in this network and analyze its structure, identifying, describing and characterizing the different positions of the actors involved in the public debate. This paper seeks to demonstrate some of the contradictions in this process and discuss the importance of ANT concepts in the research. Our data is essentially documental, composed of laws, bills, reports and official records of public debates about the net neutrality, including video recordings of seminars and public audiences promoted by the Korean National Assembly. It can be inferred that public debate about network neutrality has been revealing acute internal contradictions between interests groups, placing actors from different levels of this network in disputes which involve a constant rearrangement of positions. The findings in this study suggest that the issue is not only complicated because it is embedded contextually, but also because the respective parties' diverse interests are multifaceted and vague. It is concluded, therefore, that a coherent and consistent approach is an effective way to govern neutrality.
Keywords: 330; Network neutrality; platform neutrality; actor network theory; South Korea